Impulse Buying Era Sustainable Fashion: Peran Green Atmosphere dan Positive Emotion pada Generasi Z di Toko Pakaian Bekas - Risnawati Risnawati; Tri Wahyu Septyani; Maududi Lamparawi Magenda; Andi Indra Saputra Alamsyah; Kurniati Asmar (Komunitas Dosen Indonesia, 2025)
The background of this study is grounded in the fluctuating trend of second-hand clothing purchases, which is marked by unplanned buying among teenagers when visiting second-hand stores. Preliminary findings indicate that low impulse buying is not driven by frugal lifestyles but is influenced by store services and the overall store atmosphere. This is in line with with several studies showing, which states that shopping experience and store atmosphere are key factors in the second-hand clothing market, especially for Generation Z, who use fashion as a means of expressing themselves. This study seeks to address the existing research gap related to the relationship between store environment and impulse buying by focusing on the effect of atmosphere on impulse buying through positive emotion. The study employs an explanatory research approach with a sample of 267 customers of second-hand clothing stores in Makassar. The data were analyzed with WarpPLS version 7.0. The results show that green atmosphere has a positive yet insignificant impact on positive emotion, and also a positive but insignificant impact on impulse buying. Meanwhile, positive emotion has a positive and significant impact on impulse buying. The study concludes that although atmosphere does not produce a significant effect, consumers’ emotional factors remain the main driver of impulse buying.